Approximation of Analytic Functions by Solutions of Cauchy-Euler Equation. (6th June 2016) - Jung, Soon-Mo
Abstract : We investigate the approximation properties of a special class of twice continuously differentiable functions by solutions of the Cauchy-Euler equation.